Investigating the Level of Environmental Awareness and Practices on Recycling of Solid Wastes at University’s Campus in Malaysia - OMRAN, Abdelnaser; BAH, Muhammad; BAHARUDDIN, Amir Hussin (Journal of Environmental Management and Tourism; Vol 8 No 3 (2017): JEMT Volume VIII Issue 3(19) Summer 2017DO - 10.14505//jemt.v8.3(19).06, 2017)
The recent spate of environmental issues around the world has reinforced the need for environmental protection. One cost-effective way to protect the environment is recycling. Yet, in order to actively recycle, people’s awareness on environmental issues particularly the awareness about the effect on the environment needs to increase. In this regard, the overriding purpose of this research is to investigate the level of environmental awareness and practices on recycling of solid waste at Universiti Utara Malaysia (UUM). There are several issues hindering the recycling practices at UUM such as the abject lack of recycling among the students, lack of proper waste management and inadequate facilities to support recycling. In order to capture the level of awareness and recycling practices, questionnaire survey was distributed to students on campus. The results revealed that despite a quite number of students who had previously learnt about recycling, the environmental awareness of students was moderate. In addition, majority of students sometimes practice recycling. Subsequently, the results indicated that there is a discrepancy between learning and practice. Moreover, most of the participants ranked lack of incentive as one of the main demotivating factors to practice recycling. This study was recommended that the University should provide more recycling bins at the residential areas to stimulate the recycling practice.